Pengaruh Variasi Beban dan Kecepatan terhadap Arus Motor Hub BLDC pada Sepeda Listrik - Fariz Hernanto Oktafiandri; Eko Yudiyanto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The development of electric vehicle technology has encouraged the use of electric bicycles as an environmentally friendly and energy-efficient mode of transportation. One of the main components of an electric bicycle is the hub BLDC (Brushless Direct Current) motor, which is considered more efficient because it is directly integrated into the wheel without requiring a chain transmission system. However, the performance of the hub BLDC motor is affected by operating conditions, particularly variations in load and speed, which influence current consumption and overall electrical performance. This study aimed to analyze the effect of load and speed variations on the current consumption of a hub BLDC motor. A quantitative experimental method was employed by conducting direct tests on an electric bicycle using load variations of 50 kg, 60 kg, and 70 kg, as well as speed variations of 30 km/h, 35 km/h, and 40 km/h. Current measurements were carried out in real time using a PZEM 051 sensor, and the collected data were analyzed using average values obtained from repeated measurements. The results showed that increasing the load and speed led to higher current consumption of the hub BLDC motor, from 4.6 A to 5.0 A under load variation and from 4.5 A to 5.1 A under speed variation. These findings indicate that both load and speed significantly affect the electrical current required by the hub BLDC motor, demonstrating that greater operating demands result in higher energy consumption.